SEXUALITY, SPACE AND POWER IN BODIJA MARKET, IBADAN NIGERIA (2014)
Sexuality influences power and human relations in the market space. In spite of this role, previous studies, though abundant on the market as a space of economic transactions, have not clearly indicated the possible impact of sexuality as an element of power and human relations in the market. This study, therefore, examined how sexuality as a power relational tool and an element in social networking, affects the administration, spatial organisation, and economic transactions at Bodija market, with the aim of establishing its significance as an influential determinant of market processes. The study was guided by Foucault's Theory of Sexuality-Power Relations. Ethnographic data were collected from purposively selected organised economic-groups (EGs) in Bodija market, through qualitative methods of Participant Observation (PO), Informant interviews (IIs), Key Informant Interviews (KIIs), Focus Group Discussions (FGDs) and Life-Histories (LHs). Among Foodstuff-sellers -200IIs, 4FGDs, and 6LHs; Butchers -20IIs, 2FGDs, 2LHs; Grinders-Miller-100IIs, 2FGDs, 2LHs Soup-ingredients-traders,-10IIs, 1FGDs, 1LH, Cattle-traders -20IIs, 1FGD and the Saw-millers 30IIs, 2FGDs, 2LHs were conducted with purposively selected informants and discussants. Four KIIs were conducted with purposively selected market leaders. A total of 4 KII, 380IIs, 12FGDs and 11LHs were conducted. Data were subjected to descriptive content analysis. Four levels of hierarchical power relations were observed in Bodija market: gender, political, charismatic and persuasive. Gender, charismatic and persuasive powers cut across social networking, administration, spatial organisation and economic transactions; political power was a feature only of administration, spatial organisations and economic transaction. In social networking, Bodija market's sexuality norm accommodated paramour culture. The woman could have one "extra" sexual partner per time, while the man could have many. In both cases, paramours served as material and/or emotional support and status symbols. Women subverted male power through the manipulation of sexuality, their attractiveness, and sexuality coded speeches; some negotiated space sometimes by the offer of sex or manipulative refusal of same. In the administration, the male dominated market's power-structure, with all main EGs' executives led by male, except Soup-ingredients traders with a female leader. The male controlled market space administration, space allocation and management. Many females negotiated administrative and space concessions from males through sexual attractions. Spatial organisation was mainly controlled by male dominated leadership of EGs in collaborations with male-constituted care taker groups of the market. The market was compartmentalised along goods sold and services rendered, but several pockets of hawkers and illegal sales/transactional spaces have surfaced in different parts of the market through undue sexualisedfavour of the care-takers. As a built-up space, the market was continually restructured, thus giving the impression of being both organised and disorganised. In economic transactions, sexualised metaphors served as persuasive power. Economic transactions were indicated not only by the arrangement of stores for visibility, but also by accolades and nicknames. Four levels of hierarchical power relations in Bodija market revealed male dominance in administration and spatial organisation, female dominance in social networking and power fluidity in economic transaction. Thus, sexuality manifesting in differential expression of power, plays significant role in Bodija market space discourse.